(untitled) (Academia Science Repository, 2023)
The article is devoted to the substitution of tariff benefits in food safety. Based on scientific views of international organizations indicating the role of tariff benefits in food security and statistical data, there is an analysis of the possibilities for ensuring price stability in the domestic market.